The reflexes of syllabic liquids in ancient Greek : linguistic prehistory of the Greek dialects and Homeric Kunstsprache - Beek, Lucien van (Leiden studies in Indo-European,, 2022)
"How can we explain metrical irregularities in Homeric phrases like [androtēta kai ēbēn]? What do such phrases tell us about the antiquity of the epic tradition? And how did doublet forms such as [tetratos] beside [tetartos] originate? In this book, you will find the first systematic and complete account of the syllabic liquids in Ancient Greek. It provides an up-to-date, comprehensive and innovative etymological treatment of material from all dialects, including Mycenaean. A new model of linguistic change in the epic tradition is used to tackle two hotly-debated problems: metrical irregularities in Homer (including muta cum liquida) and the double reflex. The proposed solution has important consequences for Greek dialect classification and the prehistory of Epic language and meter"--